Change, choices, and consequences : a guide to mega thinking and planning - Kaufman, Roger A. (HPT in action series, 2006)
The decision about where an organization should be headed couldn't be more basic. Yet many organizations - both public and private - have fuzzy statements of purpose. How about yours? Do you know where you are headed? Is it the right place to go? Learn how to be proactive by defining and justifying where you should head before deciding how to get there. To help you in the process, this book introduces the concepts and tools underlying "mega thinking and planning." In 10 chapters, the author details three fundamentals for defining and delivering organizational success: A value-added fram